Gastroprotective Activity of Violacein Isolated from Chromobacterium violaceum on Indomethacin-Induced Gastric Lesions in Rats: Investigation of Potential Mechanisms of Action - Paulrayer Antonisamy; Ponnusamy Kannan; Adithan Aravinthan; Veeramuthu Duraipandiyan; Mariadhas Valan Arasu; Savarimuthu Ignacimuthu; Naif Abdullah Al-Dhabi; Jong-Hoon Kim (The Scientific World Journal)
Chromobacterium violaceum, Gram-negative bacteria species found in tropical regions of the world, produces a distinct deep violet-colored pigment called violacein. In the present study, we investigated whether violacein can promote a gastroprotective effect and verified the possible mechanisms involved in this action. For this study, an indomethacin-induced gastric ulcer rat model was used. The roles of biomolecules such as MPO, PGE2, pro- and anti-inflammatory cytokines, growth factors, caspase-3, NO, K+ATP channels, and α2-receptors were investigated. Violacein exhibited significant gastroprotective effect against indomethacin-induced lesions, while pretreatment with L-NAME and glibenclamide (but not with NEM or yohimbine) was able to reverse this action. Pretreatment with violacein also restored cNOS level to normal and led to attenuation of enhanced apoptosis and gastric microvascular permeability. Our results suggest that violacein provides a significant gastroprotective effect in an indomethacin-induced ulcer model through the maintenance of some vital protein molecules, and this effect appears to be mediated, at least in part, by endogenous prostaglandins, NOS, K+ATP channel opening, and inhibition of apoptosis and gastric microvascular permeability.